Določitev mutacije D816V v genu C-KIT pri slovenskih bolnikih z akutno mieloično levkemijo in sistemsko mastocitozo - Fink, Martina (Zdravniški vestnik, 2012)
Background: D816V mutation in the C-KIT gene is present in more than 90 % of patients with systemic mastocytosis (SM) and 2-7 % of patients with acute myeloid leukemia (AML). D816V mutation is caused by the substitution of adenine with thymine at 2447 nucleotide sequence in the C-KIT gene. This nucleotide substitution causes the replacment of aspartate acid by valine at codon 816 of the KIT protein. KIT protein with D816V mutation acts as constitutively active tyrosine kinase that promotes cell proliferation and inhibits apoptosis. The purpose of our study was to determine the incidence ofD816V mutation in the C-KIT gene in Slovenian patients with AML and in patients with suspected systemic mastocytosis. Patients and methods: In the retrospective study, 71 patients with AML and 25 patients with suspected systemic mastocytosis were included. D816V mutation in the C-KIT gene was determined by polymerase chain reaction (PCR) and the resulting PCR products were analyzed by agarose gel electrophoresis. Results: D816V mutation in KIT protein was determined in 7 % of patients with AML and in 32 % patients with suspected systemic mastocytosis. Conclusions: Identification of D816V mutation in the C-KIT gene must always be performed in patients with suspectedsystemic mastocytosis. The determination of this mutation contributesto the diagnosis and treatment selection. The finding of D816V mutation in the C-KIT gene in patients with AML and concomitant genetic modifications RUNX-RUNX1T1 (typical translocation t(8; 21) (q22, q22)) or CBFB-MYH11, which is the result of inversion on chromosome 16-(inv (16) (p13, q22)), however, indicates a faster, more aggressive course of the disease and predicts a worse outcome. The finding of the mutation in other patients with AML may indicate the presence of concomitant AML and SM, which was not found in our patients.
Keywords: acute myeloid leukemia; akutna mieloična levkemija; C-KIT; genske nepravilnosti; hematologija; krvne bolezni; levkemija; mutacije; mutation D816V; sistemska mastocitoza; systemic mastociytosis